STRATEGIC HUMAN RESOURCE MANAGEMENT BASED ON ARTIFICIAL INTELLIGENCE IN IMPROVING ORGANIZATIONAL RESILIENCE AMID GEOPOLITICAL UNCERTAINTY GLOBAL: CONTRIBUTION TO SDGs 8 AND SDGs 9 - Hesri Mintawati (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims to analyze the role of Artificial Intelligence (AI)-based Strategic Human Resource Management (SHRM) in increasing organizational resilience amidst increasing global geopolitical uncertainty and evaluate its contribution to achieving Sustainable Development Goals (SDGs) 8 (Decent Work and Economic Growth) and SDGs 9 (Industry, Innovation and Infrastructure). Global economic instability, technological disruption, and geopolitical dynamics have encouraged organizations to adopt more adaptive, data-driven, and innovation-oriented human resource management strategies to maintain the sustainability of organizational performance. In this context, the use of Artificial Intelligence technology in SHRM practices is one strategic approach to improve an organization's ability to anticipate, respond, and adapt to changes in an uncertain business environment. Study This use approach quantitative with method analysis inferential For test the relationship between capability Artificial Intelligence in management HR, practice Strategic Human Resource Management, and the level of organizational resilience. Data collection was conducted by distributing questionnaires to employees and managers in organizations that have implemented system digital HR or HR analytics. Instrument study use Likert scale 1–5, which measure AI capability indicators, technology-based SHRM practices, workforce adaptability, and organizational resilience. Data analysis was conducted using multiple regression analysis and structural model testing to identify the interplay between variables and the strategic contribution of AI to strengthening organizational resilience. The research results show that the implementation of AI-driven Strategic Human Resource Management has a positive and significant impact on increasing organizational resilience through enhanced HR analytical capabilities, data-driven decision-making, and strengthening workforce adaptability to changes in the business environment. The implementation of AI technology in the process recruitment, development competence, And management performance proven capable improving the effectiveness of talent management while strengthening organizations' capabilities in the face of geopolitical uncertainty and global economic disruption. These findings demonstrate that integrating digital technology into HR strategies not only improves organizational efficiency but also contributes to the creation of a more innovative and productive work environment. The novelty of this research lies in the development of the AI-Driven Strategic HR Resilience Framework conceptual framework, which explains how the integration of Artificial Intelligence in Strategic Human Resource Management practices can strengthen organizational resilience while supporting the implementation of SDGs 8 by improving the quality of work and workforce productivity. as well as SDGs 9 through strengthening innovation And transformation digital in management Theoretically, this research expands the study of strategic human resource management by integrating the perspectives of digital technology, organizational resilience, and sustainable development. In a way practical, study This give implications for organization in designing more adaptive, innovative, and technology-based HR management strategies to face increasingly complex global challenges.